New species of Rupirana (Heyer, 1999) (Anura, Leptodactylidae) from Serra do Assuruá, center-north of Bahia state, Brazil - Mângia, Sarah; Amaral, Guilherme do; Müller, Márcia [UNESP]; Santana, Diego J. (Institute of Vertebrate Biology, Academy of Sciences of the Czech Republic, 2025)
The Caatinga, a semi-arid region with drought-adapted vegetation, supports unique biodiversity, including numerous endemic species. Serra do Assuruá in Bahia is one such high-altitude area, rich in ecological niches but largely understudied, especially regarding amphibians, and lacks conservation units. During fieldwork, we discovered a new Rupirana species approximately 200 km beyond its known range. Previously, Rupirana had remained monotypic for over two decades, restricted to the campo rupestre ecosystem in the northern mountain ranges of Chapada Diamantina, Bahia. This unexpected finding in Serra do Assuruá prompted detailed morphological, acoustic, and molecular analyses, confirming it as a new endemic species for the region. While wind farm expansion in remote areas like the Caatinga has enabled important scientific discoveries, including this Rupirana, it also poses risks to biodiversity through habitat changes. These findings highlight the need for enhanced conservation planning in the Caatinga biome, as such discoveries underscore both the ecological value and the vulnerability of these fragile ecosystems. Therefore, balancing renewable energy development with conservation efforts through rigorous environmental assessments is essential to protect these fragile ecosystems.
Keywords: amphibia; Caatinga; conservation; taxonomy